The rise of the impulsive shopper - Farah, Maya (2018)
The Amazon Dash Button technology allows customers to remotely reorder products by the mere press of a button. To investigate the impact of this tech disruption on the consumer journey, a survey was completed by 630 U.S. Dash Button users. The findings show that its usage significantly affects shopping impulsiveness.